The Impact of ERP system on Sales Invoice Printing Process - Ria Nur Fitriani; Yayan Haryanto (PT Larva Wijaya Penerbit, 2022)
Sales invoice is proof of sale of goods and services that shows the amount entitled to be billed to customers for a purchase of goods or services. The aims of the research is to find out whether the ERP system has an impact on the sales invoice printing process at PT. Timah Industri, tbk. The data analysis technique uses secondary data and primary data based on the results of interviews or direct observations. The result of the research is the ERP system has impact on sales invoice printing process. The implication of the research is the implementation and the use of ERP system on sales invoice printing process can be easily to integration sales processes, especially on sales invoice printing processes.